Spatial and temporal patterns in symptom expression within eight woodlands affected by Acute Oak Decline - Brown,N; Jeger,M; Kirk,S; Xu,X; Denman,S (Forest Ecology and Management, 2015)
Acute Oak Decline (AOD) is a newly defined condition in the UK that forms a distinct component within the wider oak decline complex. It can be identified by distinctive stem symptoms, dark liquid seeping out between the bark plates from areas of necrosis in the cambial tissue, which are found in conjunction with signs of the two spotted oak buprestid Agrilus biguttatus. Novel bacterial species have been isolated from the inner bark necrosis, but little is known regarding the spatial and temporal patterns of AOD symptoms expression. This study presents the results from eight plots across southern and central England monitored for three to four years between 2009 and 2012. These data give a first description of the epidemiology of AOD. Findings suggest affected trees occur in localised clusters rather than at random through the plots, pointing to biotic rather than wider scale environmental effects such as drought. In addition, contagion (spread of symptoms between neighbouring trees) was demonstrated. Previously, mortality was described as occurring soon after infection; current data suggests this is longer than two years. 23.5% of oak with both stem bleeds and exit holes in 2009 died during the monitoring period. Exit holes were observed on hosts for the first time in the final years before death linking them to the later stages of decline. Finally, a large proportion of lightly infected individuals have been shown to form callus over the previous year’s stem symptoms and enter remission. This finding suggests host resistance may provide some scope for management of AOD.